Indications and contraindications for infusing specific amino acids (leucine, glutamine, arginine, citrulline, and taurine) in critical illness. Issue 2 (March 2016) - Ginguay, Antonin; De Bandt, Jean-Pascal; Cynober, Luc
Abstract : Purpose of review: The review assesses the utility of supplementing parenteral or enteral nutrition of ICU patients with each of five specific amino acids that display pharmacological properties. Specifying indications implies also stating contraindications. Combined supplementation of amino acids with ω3-fatty acids and/or trace elements (immune-enhancing diets) will not be considered in this review because these mixtures do not allow the role of amino acids in the effect (positive or negative) of the mixture to be isolated, and so cannot show whether or not supplementation of a given amino acid is indicated. Recent findings: After decades of unbridled use of glutamine (GLN) supplementation in critically ill patients, recent large trials have brought a note of caution, indicating for example that GLN should not be used in patients with multiple organ failure. Yet these large trials do not change the conclusions of recent meta-analyses. Arginine (ARG), as a single dietary supplement, is probably not harmful in critical illness, in particular in a situation of ARG deficiency syndrome with low nitric oxide production. Citrulline supplementation strongly improves microcirculation in animal models with gut injury, but clinical studies are lacking. Taurine has a potent protective effect against ischemic reperfusion injury. Summary: Amino acid-based pharmaconutrition has displayed familiar 'big project' stages: enthusiasm (citrulline and taurine), doubt (GLN), hunt for the guilty (ARG), and backpedalling (leucine). Progress in this field is very slow, and sometimes gives way to retreat, as demonstrated by recent large trials on GLN supplementation.